Change in functional profile after lumbar spinal surgery: a register-based study among 1,451 patients - Koivunen; Konsta K J; Widbom-Kolhanen, Sara S; Pernaa, Katri I; Arokoski; Jari P A; Saltychev, Mikhail (MJS Publishing, Medical Journals Sweden AB, 2025)
Background and purpose: The Oswestry Disability Index has usually only been used as a composite score but, according to previous studies, disability caused by back pain may be too broad a concept to be explained by a single number. We aimed to analyze changes in each ODI item's score from preoperative to 3, 12, and 24 months after surgery by creating a functional profile.
Methods: This was a register-based study of 1,451 patients undergoing lumbar spinal surgery between 2018 and 2021. The patients responded to a repeated survey preoperatively and 3, 12, and 24 months after surgery. The significance of change in the ODI items' scores was assessed by a symmetry test.
Results: All the ODI items' scores and total score improved between baseline and 3-month follow-up (P < 0.001). The magnitude of this improvement varied across different items. After 3 months, no significant change was seen for most of the items.
Conclusion: During a postoperative 2-year follow-up, individual items of the ODI demonstrated changes of different magnitude. The results imply that the use of a single composite score of the ODI might be insufficient to describe changes in functioning among patients undergoing lumbar spinal surgery. Instead, in some situations, creating a functional profile based on the scores from individual items may be a better solution to describe the changes in disability level.